ASSOCIATED FACTORS OF FAMILY RESPONSE TO PATIENTS WITH SEVERE PSYCHIATRIC DISORDERS IN SANGATTA UTARA - Sitorus, Rame; Pakki, Irfansyah Baharuddin; Anggraeni, Ike (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: Mental disorders affect approximately 20% of Indonesia’s population, with East Kalimantan reporting 2,679 cases, including 130 in the Sangatta Utara area. Despite the growing awareness of the critical role families play in supporting individuals with mental disorders, there is a still lack of studies that specifically explore family responses, particularly in Indonesia. This study aims to fill this gap by examining the factors that are associated with family responses to individuals living with severe mental disorders in Sangatta Utara, East Kalimantan.Methods: This observational and cross-sectional study targeted 130 families of individuals diagnosed with severe mental disorders. Data were collected using structured questionnaires. Statistical analysis was performed using chi-square tests and binary logistic regression. This statistical model aimed to identify the factors most influential on family responses.Results: Significant associations were found between family burden, social support, and family responses to individuals with severe mental disorders. The analysis revealed that family burden was strongly associated with positive family responses (Exp(B) = 24.22, p = 0.002), indicating that higher caregiving burden significantly increased the likelihood of positive family responses. Similarly, social support showed a significant positive association with family responses (Exp(B) = 5.19, p = 0.040).Conclusion: Family burden and social support are important factors that influence family responses to severe mental disorders. This study emphasizes and suggests the importance of targeted family counseling and community-based support programs in North Sangatta.